The Effect of Risk Management and Earnings Quality on Firm Value with Good Corporate Governance as a Moderating Variable in Banking Companies Listed on the Indonesia Stock Exchange (2020–2024) - Ajeng Indah Kusuma; Eva Herianti (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study aims to analyze the effect of risk management and earnings quality on firm value, as well as to examine the moderating role of Good Corporate Governance (GCG) in banking companies listed on the Indonesia Stock Exchange during the 2020–2024 period. Earnings quality in this study is proxied by Loan Loss Provision (LLP), which reflects earnings management practices in the banking sector. The study employs a quantitative approach using multiple linear regression and Moderated Regression Analysis (MRA). The data used consist of simulated panel data for learning purposes, constructed consistently with the characteristics of the banking industry. The results indicate that risk management has a positive effect on firm value, while earnings quality proxied by Loan Loss Provision has a negative effect on firm value. Furthermore, Good Corporate Governance is proven to strengthen the influence of risk management on firm value and weaken the negative effect of earnings quality on firm value. These findings suggest that the implementation of good corporate governance plays a crucial role in enhancing the effectiveness of risk management and limiting opportunistic managerial behavior. This study contributes theoretically to the development of agency theory literature and provides practical implications for banking management and investors in enhancing firm value sustainably.